The Impact of Competencies, Information Search, and Competitive Strategy on the Export Performance - Elitan, Lena (Universitas Prasetiya Mulya, 2011)
This confirmatory study is aimed at analyzing the impact of relationships, information search, and competencies on competitive strategy and SMEs performance in Indonesia. The study used 100 SMEs samples that obtained through mailed questionnaires. The results show: Firstly, the perception of information, information sources, and export competence has no significant effect on competitive strategy. However the findings for SMEs in Indonesia, indicated that export related information has negative effects on competitive strategy. Secondly, export competencies has an enormous influence on the company’s capacity and ability to use information appropriately, when the company must deal with challenges or when the company is eager to take advantage of the opportunities to increase growth and profitability. Thirdly, competitive strategy does not directly affect export performance but it is moderated by the environment uncertainty. It indicates that the influence of competitive strategy would be greater in an uncertain business environment. The uncertain business environment will encourage companies to explore competitive strategy to improve their performance.